Immune microenvironment changes of liver cirrhosis: emerging role of mesenchymal stromal cells - Yi, Qiuyun; Yang, Jinxian; Wu, Ying; Wang, Ying; Cao, Qiqi; Wen, Wen (Frontiers in Immunology, 2023)
Cirrhosis is a progressive and diffuse liver disease characterized by liver tissue fibrosis and impaired liver function. This condition is brought about by several factors, including chronic hepatitis, hepatic steatosis, alcohol abuse, and other immunological injuries. The pathogenesis of liver cirrhosis is a complex process that involves the interaction of various immune cells and cytokines, which work together to create the hepatic homeostasis imbalance in the liver. Some studies have indicated that alterations in the immune microenvironment of liver cirrhosis are closely linked to the development and prognosis of the disease. The noteworthy function of mesenchymal stem cells and their paracrine secretion lies in their ability to promote the production of cytokines, which in turn enhance the self-repairing capabilities of tissues. The objective of this review is to provide a summary of the alterations in liver homeostasis and to discuss intercellular communication within the organ. Recent research on MSCs is yielding a blueprint for cell typing and biomarker immunoregulation. Hopefully, as MSCs researches continue to progress, novel therapeutic approaches will emerge to address cirrhosis.